WHITE PAPER: Ideas and Recommendations “WAY FORWARD FOR SCIENCE IN UKRAINE: Perspective of the Ukrainian Research Diaspora” - Seumenicht, O.; Garaschuk, O.; Ladokhin, O. (Science and Innovation, 2024)
Introduction. A wider involvement of scientific diaspora can be an important approach to reforming the scientific system of Ukraine and to developing its innovation environment. The first Forum of the Ukrainian Scientific Diaspora “Advancing Science through International Cooperation” (Kyiv, October 20—22, 2018) has provided an excellent platform to address this issue. Problem Statement. The current state of the scholarly research and educational areas in Ukraine is characterized by several negative phenomena and requires systematic reforms. Purpose. To summarize the discussed ideas and to formulate recommendations on the prospects for the development of science in Ukraine, based on contributions of the Forum participants. Materials and Methods. Ideas and suggestions discussed while preparing the agenda, presentations, round tables, panel discussions and feedback survey have been analyzed. In addition, some examples of relevant international funding programs and initiatives aiming at intensifying cooperation with diaspora scholars have been studied. Results. A series of measures aiming at addressing the issue of internal and external “brain drain” from science, promoting “brain circulation”, and increasing the intellectual potential of the society has been proposed. These measures include, in particular, increasing the base funding of science, introducing favorable tax regulations for the international cooperation projects, improving the national intellectual property rights legislation, and creating opportunities and building the capacity for establishing joint grant programs with international partners, co-funding joint laboratories, etc. Moreover, it has been stressed that it is crucially important to establish expert committees with the mandatory participation of foreign experts for reviewing R&D projects and scholarly research publications, evaluating R&D institutions and contributing to the reforms. Examples of international programs and funding schemes aiming at cooperation with diaspora scholars have been shown. Conclusions. The Forum of Scientific Diaspora offers a fruitful discussion platform for presenting and discussing research results of Ukrainian and international researchers, as well as for addressing the most pressing issues regarding the current state of Ukrainian science. Our compatriots are eager to share their knowledge and experience gained from leading research organizations in different countries to promote the reforms and the development of science in Ukraine.